Enhanced photocatalytic detoxication properties of OVs-rich Pd/N–TiO2 heterojunctions: excellent charge separation and mechanism insight. (March 2023) - Zhang, T.; Chen, Y.; Yang, X.; Chen, J.; Zhong, J.; Li, J.; Li, M.; Wan, Z.
Abstract: Improving the separation efficiency of photoinduced carriers and light absorption range is a crucial target to improve the photocatalytic properties of wide-band semiconductor photocatalysts. In this work, OVs-rich Pd/N–TiO2 was prepared by a sol-gel method. The results display that N doping and construction of OVs can meliorate the energy band structure of TiO2 based on the various characterizations. The surface plasmon resonance (SPR) effect of Pd 0 particles, N doping and introduction of abundant OVs play a synergistic role, which elevates the separation efficiency of photoinduced charge pairs effectually and further enhances the photocatalytic properties of the catalysts. The Density Functional Theory (DFT) calculations solidly support that the construction of Schottky heterojunctions and the transfer of electrons from N–TiO2 to Pd 0 particles, enabling efficient separation of photoinduced e − /h + pairs. The strengthened photocatalytic performance of the optimized TiO2 can be contributed to the enhanced visible light absorption and the effective separation and migration of photogenerated carriers of catalysts. The results of photocatalytic degradation of two typical contaminants (phenol and RhB) reveal that OVs-rich Pd/N–TiO2 samples show superior activity than the reference N–TiO2 . This work highlights a simple and effective method that can be used to prepare TiO2 composites with excellent photocatalytic properties. Highlights: OVs-rich Pd/N–TiO2 was prepared through a sol-gel method. Pd 0 particles, N doping and OVs reduce the band gap of TiO2 . The Schottky heterojunctions increase the separation efficiency of photoinduced carriers. OVs-rich Pd/N–TiO2 sample exhibits superior activity than the reference N–TiO2 .